Paralely mezi slovinským a českým dramatem 60. let - Jensterle Doležal, Alenka (Slavia Centralis, 2020)
Parallels between Slovenian and Czech poetic drama in the 1960sThis article concentrates on the parallels between Slovene and Czech poetic drama in the nineteen sixties. I recognise similarities between the playwrights Dane Zajc, Josef Topol, and Gregor Strniša. Comparative analysis of Zajc’s and Topol’s texts exposes similar intimate themes, such as motives of love and the phenomena of time. The most vivid comparison is between Topol’s play Slavík v večeří and Strniša’s play Ljudožerci. In both plays, the dramatic plot is constructed as grotesque and absurd play. The dramatic perspective shows the experience of the absurd in the world.
Keywords: Slovene poetical Drama; Czech poetical Drama; Central European Literature in 1960s; Comparision of Slovene and Czech Literature